Analyzing The Merging Effect of Agro-Production and Formal Training On Women-Empowerment in Rural-Bangladesh - Sathi Mary Baroi (Social Sciences and Education Research Review)
Bangladesh's agricultural sector is crucial to its economy, and women's participation is emphasized for empowerment and increased agro-production. This study uses a household survey of 200 women in four rural Bangladeshi villages to analyze the impact of independent variables (agricultural production, training facility, media connection) on women's empowerment in the agricultural sector (WEIA). Multiple regression analysis shows that agricultural production, training facility, and media connection positively and significantly influence WEIA. The interaction of agricultural production and training facility also has a positive and significant impact. The findings suggest policy implications for sustainable agriculture and women's empowerment.